ANALISIS PROKSIMAT PADA TEPUNG BIJI NANGKA (Artocarpus Heterophyllus Lamk.) - ESTI NOVI ANDYARINI; IRUL HIDAYATI (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2017)
Indonesia is a tropical country which is diverse types of plants, one of them which was plant jackfruit (Artocarpus heterophyllus Lamk.). But so far, its utilization of waste still leaves form the seeds of jackfruit. Basic human needs of food and technology progress encourages humans to cultivate seeds into flour, jackfruit seed jackfruit. To understand the nutrient content of quality food grain powder jackfruit is the researchers want to do an analysis of proksimat on seed flour, jackfruit. This research use experimental design to test the levels of protein, carbs, fat and calories jackfruit seed flour. The measurement of protein content by Kjeldahl method, method of Carbohydrate carbs by Defference method with Soklet,fat,and calories with manual calculation. Research results from the jackfruit seeds have been processed into flour, jackfruit seeds showed that levels of the protein in the flour biji nangka of 12.19 grams, carbohydrate levels of 56.21 grams, 1.12 grams of fat content and moisture content of 12.4 grams. Expected with the known value of jackfruit seeds flour on proksimat this will encourage the public to make use of waste food into jackfruit seeds in the form of jackfruit seed flour. In addition to reducing waste, nutrient content of jackfruit seed flour is also high.